Efecto del extracto hidroalcohólico de Salvia hispanica “chía” sobre la absorción intestinal de la glucosa en Rattus rattus var. Albinus. - Simón Gómez, Reyna Isabel (2016)
The purpose of this study was to determine the effect of alcoholic extract hipanica Salvia on the intestinal absorption of glucose in Rattus rattus var. Albinus_x000D_ They worked in five groups of rats with five individuals each. A negative control group, positive and experimental at different doses of the extract chia Control; each individual was anesthetized with sodium pentobarbital and dissected small intestine dividing it into duodenum, jejunum and ileum was extracted._x000D_ Each serving individual was placed in a system of incubation at 37 ° C in Tyrode solution with continuous oxygenation, the negative control group without treatment, the positive control with 10% glucose and experimental with 10% glucose plus 100, 300 and 500mg / dL of alcoholic extract of "chia" respectively._x000D_ Samples of liquid contained in each portion of the intestine, at 0, 30, 60, 90 and 120 minutes, performing the assay of glucose read in spectrophotometer SPECTRONIC 20-530 nm were obtained. It was found that the hydroalcoholic extract of seeds of Salvia hispanica a concentration of 500 mg / dL significantly decreases intestinal absorption of glucose in the duodenal portion Rattus rattus var. Albinus while in the jejunum and ileum glucose uptake was not significant.